Influence and effects of the support’s space dimension on the estimation of mineral resources - Maldonado Escalante, Carlos Enrique (2022)
The mineral resources´ estimation is a fundamental issue in the existence of a mining-metallurgical company. The amount of current software and methods has allowed the quality of the estimates that are made to increase, however, there are still variables that are determined based on criteria and experience that influence the accuracy of the generated model. In geostatistics, the size of the support is of great importance for the creation of the model. In this work, two block models of different support are compared, created from the same data, with the same estimation criteria, to recognize the difference between the two, and the real production data, concluding that no significant variation is observed on this scale.